The triple bottom line, does it all add up? : assessing the sustainability of business and CSR - Henriques, Adrian, 1954-; Richardson, Julie (Earthscan, 2004)
In this text leading experts examine the implications of the idea of the "triple bottom line"--The business strategy that delivers simultaneous financial, social and environmental benefits - showing what it has already achieved by stimulating change and bringing business to appreciate the importance and benefits of corporate social responsibility (CSR) and good environmental performance. They then go beyond this to explore the limits of the metaphor and what remains to be done through regulation and legislation and with detailed professional procedures in environmental accounting and management and social auditing. They show how much more attention is now being focused by business on delivering more than just financial targets, and make clear where the next steps must be taken in continuing along this trajectory